Evaluation of the Sustainability of Implementing the P5 Worksheet for Strengthening Student Character at SMAN 1 Terara - Susilawati, Susilawati; Doyan, Aris; Nisrina, Nina; Ayub, Syahrial; Busyairi, Ahmad (Unram Journal of Community Service, 2024)
This study examines the sustainability of implementing the P5 Worksheet in strengthening student character at SMAN 1 Terara, focusing on several related variables: cooperation, discipline, and responsibility. The research employs a descriptive approach with a mixed-method design, combining qualitative and quantitative analyses to understand the worksheet's impact on student character. Data were collected through classroom activity observations, in-depth interviews with teachers, and questionnaires completed by teachers to measure the dimensions of student character. The findings indicate that the P5 Worksheet is effective in enhancing student cooperation, despite challenges such as limited time, students' difficulties in understanding instructions, and the relevance of content to the local context. Additionally, limited institutional support was found to affect the smooth implementation of the program. Based on these findings, it is recommended to adjust the worksheet materials, improve teacher training, and strengthen support from the school to enhance the effectiveness and sustainability of the P5 Worksheet in fostering student character development.